Impact Forces of Walking and Running at the Same Intensity. Issue 4 (April 2016) - Swain, David P.; Kelleran, Kyle J.; Graves, Melani S.; Morrison, Steven
Abstract : Abstract: Swain, DP, Kelleran, KJ, Graves, MS, and Morrison, S. Impact forces of walking and running at the same intensity. J Strength Cond Res 30(4): 1042–1049, 2016—Moderate-intensity walking (horizontal, WH ), vigorous-intensity walking (incline, WI ), and vigorous-intensity running (horizontal, R) were compared. The hypothesis is that running creates greater loading forces than walking even at the same aerobic intensity. Young adults (10 M and 10 F; age, 22.8 ± 0.5 years) performed 3 exercise trials in a counter-balanced order: walking 5.5 kph at 0% grade (WH ); walking 5.5 kph at 11% (WI ); and running at 8.0 kph at 0% (R). Oxygen consumption (V[Combining Dot Above]O2 ), step frequency, peak vertical ground reaction force (VGRF), and vertical force loading rate were recorded during the last 5 minutes of each trial. Results are mean ± SE . Net V[Combining Dot Above]O2 during WH (10.5 ± 0.3 ml·min −1 ·kg −1 ) was significantly less than WI (26.3 ± 0.3) and R (25.1 ± 0.7 ml·min −1 ·kg −1 ). Step frequency was significantly greater during R (163 ± 1.5 steps per minute) than both walking conditions (WH, 128 ± 1.0 steps per minute; WI, 126 ± 1.2 steps per minute). Peak VGRF was significantly greater during running (844 ± 47 N) than both walking conditions (WH, 581 ± 27 N; WI, 565 ± 28 N). Force loading rate was significantly greater with R (8, 214 ± 26 N·s −1 ) than WH (6, 497 ± 15 N·s −1 ) and WI (5, 699 ± 16 N·s −1 ), with WH > WI . Vigorous-intensity walking produced no greater loading forces than moderate-intensity walking. However, running at a vigorous intensity produced substantially greater loading forces than walking of the same intensity. These findings suggest that vigorous aerobic exercise may be performed without elevated orthopedic stress, depending on the mode prescribed.